2023
DOI: 10.1126/sciadv.ade2493
|View full text |Cite
|
Sign up to set email alerts
|

Auxin promotes hypocotyl elongation by enhancing BZR1 nuclear accumulation in Arabidopsis

Abstract: Auxin and brassinosteroids (BRs) are two major growth-promoting phytohormones that shape hypocotyl elongation; however, the cross-talk between auxin and BR in this process is not fully understood. In this study, we found that auxin-induced hypocotyl elongation is dependent on brassinazole-resistant 1 (BZR1), a core BR signaling component. Auxin promotes BZR1 nuclear accumulation in hypocotyl cells, a process dependent on mitogen-activated protein kinase 3 (MPK3) and MPK6, which are both activated by auxin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…1G). It remains possible that 14-3-3 mediated cytosolic retention of BZR1 represents the central regulatory event in planta (Gampala et al, 2007; Lozano-Durán et al, 2014; Ryu et al, 2007; Tang et al, 2011; Yu et al, 2023). The range of binding affinities (∼0.5 - ∼20 µM) observed for the various 14-3-3 – BR component interactions is comparable to what has been previously reported for some (Gao et al, 2014), but not all (Fuglsang et al, 2003; Latz et al, 2007; Ottmann et al, 2007) 14-3-3 – protein interactions in plants.…”
Section: Discussionmentioning
confidence: 99%
“…1G). It remains possible that 14-3-3 mediated cytosolic retention of BZR1 represents the central regulatory event in planta (Gampala et al, 2007; Lozano-Durán et al, 2014; Ryu et al, 2007; Tang et al, 2011; Yu et al, 2023). The range of binding affinities (∼0.5 - ∼20 µM) observed for the various 14-3-3 – BR component interactions is comparable to what has been previously reported for some (Gao et al, 2014), but not all (Fuglsang et al, 2003; Latz et al, 2007; Ottmann et al, 2007) 14-3-3 – protein interactions in plants.…”
Section: Discussionmentioning
confidence: 99%
“…shown to positively regulate this process (Yu et al, 2011) while BZR1 acts on more downstream responsive genes (He et al, 2005). The increased BZR1 signal could stem from the high levels of auxin in the CIM treatment, as a previous study has shown induced nuclear localization of BZR1 in the hypocotyl, under auxin-induced elongation (Yu et al, 2023). Additionally, auxin and BR share overlapping activities in the promotion of LR (Bao et al, 2004;Chaiwanon and Wang, 2015;Li et al, 2005;Mazzoni-putman et al, 2021) suggesting a possible positive role for BZR1 in upregulating targets important for callus formation.…”
Section: Cim and Sim Promote Different Fates For Bes1 And Bzr1 Expres...mentioning
confidence: 91%
“…These two hormones are known to share several target genes and have overlapping activities notably in the promotion of LR formation (Bao et al, 2004; Chaiwanon and Wang, 2015; Kim et al, 2007; Li et al, 2005; Mazzoni-putman et al, 2021). Auxin has been shown to promote BZR1’s nuclear accumulation and direct binding and transcriptional control of ARF7 during hypocotyl elongation (Yu et al, 2023), thus establishing a direct molecular link between BZR1 and auxin signaling pathway (Zhou et al, 2013). Similarly, BIN2 has been shown to be a positive regulator of LR organogenesis (Cho et al, 2014) and callus formation (Lee and Seo, 2017) through direct regulation of ARF7 and ARF19.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, auxins have some inhibiting role in roots growth. IAA is one of the major and most common auxins produced by plants, which stimulates plant growth [38,39].…”
Section: Interaction Of Brassinosteroids With Auxins In Plant Cellsmentioning
confidence: 99%
“…The overexpression of PIN-LIKES auxin transporters in imp mutants strongly influences BR signaling, possibly by changing local auxin levels [52]. Auxins and BRs stimulate growth and affect the elongation of the hypocotyl, but the hormone crosstalk mechanism implicated in this process is not fully clear [39,53]. BRs also stimulate auxin levels important for the induction of lateral roots grown under low nitrogen stress by inducing the AtYUC5, AtYUC7, and AtYUC8 auxin biosynthetic genes.…”
Section: Interaction Of Brassinosteroids With Auxins In Plant Cellsmentioning
confidence: 99%